Comprehensive Digital Transformation in Retail: An Enterprise Resource Planning and Advanced Technology Integration Framework - Vaishnav Yerram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the comprehensive transformation of retail operations through Enterprise Resource Planning (ERP) systems and advanced digital technologies. The article examines the evolution of retail management systems across multiple dimensions, including financial intelligence, inventory management, customer experience, and data security. It analyzes how modern retail environments leverage sophisticated technologies such as LPWAN, artificial intelligence, and machine learning to create seamless integration between physical and digital channels. The article investigates the implementation of intelligent document recognition systems, automated financial processes, and advanced analytics capabilities that enhance decision-making accuracy and operational efficiency. Furthermore, it explores how unified customer data integration and behavioral analysis enable retailers to deliver personalized experiences while maintaining robust security measures. The article also delves into the transformation of warehouse operations through automation technologies and the integration of e-commerce platforms, highlighting how these advancements contribute to improved order fulfillment and inventory optimization. The article emphasizes the importance of future-ready implementation strategies and emerging trends in retail technology.
Keywords: Enterprise Resource Planning (ERP); Retail Automation; Data Integration; Customer Experience Management; Digital Transformation